(untitled) (Journal of Mechanical Engineering, 2015)
Borehole instability during drilling is common in shale formation. Weak bedding plane in borehole is critical in understanding in-situ stress and borehole instability. Unified decision about the plane of weakness and failure of borehole on shale has yet to be fully realized by the industry, particularly because borehole stability has not been well addressed. This research was based on a linear elastic and isotropic model for stresses around the wellbore with the aim of trying to understand the general behaviour of inclined borehole failure due to bedding plane. Using Aadnoy et. al (2009)s model, this paper discussed mechanical wellbore stability and plane of weakness of shale formation. This paper investigated three major factors firstly, borehole failure of bedding plane, secondly it introduced optimized well path. Thirdly, it analysed whether well data was present at a safe position or bedding exposed positions. This paper also analysed the 3D effect of attack angle changing azimuth with a constant inclination on bedding plane. This paper argues that bedding exposed does not only depend on inclination but also depend on dip of the formation, attack angle and azimuth. It also found the different value of attack angle of up dip and down dip position of Aadnoy model and addressed way to solve the existing difficulty